2019
DOI: 10.1002/ehf2.12532
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic utility of diastolic dysfunction and speckle tracking echocardiography in heart failure with reduced ejection fraction

Abstract: Aims We hypothesized that grading of diastolic dysfunction (DDF) according to two DDF grading algorithms and strain imaging yields prognostic information on all‐cause mortality in patients with heart failure with reduced ejection fraction (HFrEF). Methods and results We enrolled ambulatory HFrEF (left ventricular ejection fraction < 45%; N = 1 065) patients who underwent echocardiography and speckle tracking assessment of global longitudinal strain (GLS). Patients were stratified according to DDF grades (Grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…However, E/e ′ and LA volumes did not increase, suggesting that such changes were not associated with an increase in cardiac filling pressures. Moreover contribute to morbidity in HFrEF, 19,20 treatment with a cardiac myosin activator that preserves relaxation may lead to enhanced clinical benefits. Consistent with the pre-clinical ex vivo and in vivo findings of direct atrial activation, danicamtiv had pronounced effects on LA volume and function, with concentration-dependent reductions in LA minimum volume and increases in LAEF and LAFI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, E/e ′ and LA volumes did not increase, suggesting that such changes were not associated with an increase in cardiac filling pressures. Moreover contribute to morbidity in HFrEF, 19,20 treatment with a cardiac myosin activator that preserves relaxation may lead to enhanced clinical benefits. Consistent with the pre-clinical ex vivo and in vivo findings of direct atrial activation, danicamtiv had pronounced effects on LA volume and function, with concentration-dependent reductions in LA minimum volume and increases in LAEF and LAFI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since forward flow (SV) remained enhanced, any effects of the potentially slowed relaxation on diastolic filling may have been offset by improved atrial systolic performance, in the setting of unaltered ventricular stiffness. Since diastolic dysfunction may contribute to morbidity in HFrEF, 19,20 treatment with a cardiac myosin activator that preserves relaxation may lead to enhanced clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that diastolic dysfunction (DD) is associated with increased mortality in patients with HF and reduced ejection fraction (3), (4). The best modality to assess diastolic function in CRT-candidates is an object of debate and the relationship between diastolic function, CRTresponse and survival is not definitely understood (5).…”
mentioning
confidence: 99%
“…As compared to normal DF, any Ddys grade had significant hazard ratios for the composite outcome. Hansen 34 compared the use of the algorithm by the ASE/EACVI and Johansen's for prediction of ACM over 3 years in a cohort of 546 patients with HFrEF and demonstrated that the hazard ratio = 1.09 for ASE/EACVI for grade 1 versus grade 3 Ddys and 2.236 for Johansen's algorithm for grade 2 versus grade 3 Ddys. The AUC = .604 for ASE/EACVI and .625 for Johansen's algorithm, which are slightly higher than our data.…”
Section: Discussionmentioning
confidence: 99%